2006
DOI: 10.1111/j.1464-410x.2006.06404.x
|View full text |Cite
|
Sign up to set email alerts
|

Introital ultrasonography: a comparison of women with stress incontinence due to urethral hypermobility and continent women

Abstract: at rest and on straining. Several distances were measured to determine if any provided an objective distinction between continent and incontinent women. RESULTSAmong all the IUS variables assessed, sliding (calculated as the difference between the distance urethra-bladder neck, U-BN, at rest and under stress) was the best for distinguishing continent and incontinent women. The receiver operating characteristic curves showed that with a threshold of 8 mm, sliding had a sensitivity of 92% and a specificity of 79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…This result was as expected. The action of the PFMs has been shown to hold the urethra in place such that it can be compressed between that anterior vaginal wall and the PS during tasks that increase intra‐abdominal pressure . As such, a reduction of bladder neck excursion during coughing is an expected outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was as expected. The action of the PFMs has been shown to hold the urethra in place such that it can be compressed between that anterior vaginal wall and the PS during tasks that increase intra‐abdominal pressure . As such, a reduction of bladder neck excursion during coughing is an expected outcome.…”
Section: Discussionmentioning
confidence: 99%
“…pressure. 4,[14][15][16] As such, a reduction of bladder neck excursion during coughing is an expected outcome. Conversely, a properly performed Valsalva maneuver involves complete relaxation of the PFMs, 28,30 and therefore challenges the passive resistance of the PFMs and endopelvic fascia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have used women with symptoms of lower urinary tract dysfunction in the absence of stress incontinence during evaluation as controls [14]. Another study utilized a control group with significant differences from the study group in both age and parity [15]. Having controls that are younger than cases with SUI could bias the results and may be partly responsible for earlier studies revealing greater differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the use of ultrasound in evaluation of bladder neck mobility, some authors found a lower mean bladder neck descent in continent women than in incontinent women during straining [36,37].…”
Section: Discussionmentioning
confidence: 99%